Modal dasar rohaniah dan mental dalam GBHN menurut pandangan Islam sebagai tolok ukur pembangunan bangsa dan negara (Lembaga Penelitian, Universitas Islam Djakarta, 1993)
Basic principle of the mental and spiritual contents of GBHN, broad outlines of the state policy, according to Islamic viewpoint with reference to national development.